Paper or Facebook? An experiment on the comprehension of texts with a group of dropouts - Federico Batini; Marco Bartolucci (Firenze University Press, 2015)
Reading texts on the web using technological devices is a practice that is increasing, especially among the younger generation, and this raises questions about the skills that are required to do this, the role and effects of the distractors present around the text, and the cognitive reorganisation that involves a change in the tools used for reading. It appears possible to hypothesise that the meaning of texts is destined, in time, to be more accessible through technological devices rather than via paper. This article presents the results of an experiment conducted with a group of dropouts, a category identified for placement outside the classic route of education, and therefore further removed from the daily use of traditional, printed texts encountered in a professional training course. Using evidence from the survey released by OECD-PISA, our intention is to compare the understanding of these texts when presented on paper compared to when they appeared on Facebook.